Chemistry, biocidal and antioxidant activities of essential oil and oleoresins from piper cubeba (seed) - Singh, Gurdip (2008)
The hydrodistilled Piper cubeba (tailed pepper) essential oil and various oleoresins individually collected by soxhlet apparatus using methanol, ethanol, petroleum benzene, diethyl ether and chloroform as solvents were tested for antimicrobial and antioxidant activities. The essential oil and oleoresins were analyzed by GC and GC/MS techniques. The main component of the essential oil was ß-cubebene (18.94 %) followed by cubebol (13.32 %), sabinene (9.60 %), α-copaene (7.41%) and ß-caryophyllene (5.28%) with many other components in minor amounts. All the oleoresins showed the presence of 85 components. The major component in all the oleoresins was cubebol (stereoisomer). The percentage of cubebol in the diethyl ether extract was 32.38, in the ethanol extract 25.51, in the petroleum benzene extract 42.89, in the chloroform extract 28.00 and in methanol extract 19.03. The essential oil and oleoresins were tested using different in vitro antioxidant and antimicrobial activities. The antioxidant activity of the essential oil and oleoresins was tested in mustard oil and the antimicrobial results were compared to commercial antifungal and antimicrobial agents after appropriate clinical trials.